Representation of Multicultural Identity Through Old Houses and Displays: Case Study of Lasem, Indonesia - Virliany Rizqia Putri (Journal of Visual Art and Design, 2023)
Lasem, located in Central Java, Indonesia, is an area where diverse cultural and religious groups, such as Javanese, Chinese, and Muslim communities coexist. In recent years, old houses that are considered heritage in Lasem have been revitalized and opened as commercial spaces such as guest houses, restaurants, and/or museums, displaying their collections to the public. This paper discusses cultural representation through the display of heritage buildings or artifacts. Employing qualitative methods with purposive sampling, three specific old houses located in Lasem were chosen as case studies: Rumah Oei, Rumah Merah, and Nyah Lasem. Similarities can be drawn between the three houses, in that they displayed old and new objects, combined to construct and represent the values, ideas, and meanings that are wanted to be exhibited by the exhibitors. Further research is needed to analyze the actual selections and curatorial system for the displays in each house.